Chlamydia pneumoniae and atherosclrerosis: pathogenic ways - Woolcott, Orison (2002)
Atherosclerosis is a chronic inflammatory process in which macrophages, smooth muscle cells, T lymphocytes, and several chemical mediators intervene. In recent years, the finding of Chlamydia pneumoniae in arterial atherosclerotic plaques has suggested an etiological role; however, whether C. pneumoniae causes atherosclerosis or precipitates or favors atheroesclerosis progression remains uncertain. We review studies published on-line or available in Lima specialized libraries regarding C. pneumoniae and atherosclerosis association, with special emphasis on the pathogenic role of this bacteria.